Business Guide to Trade Remedies in the United States - International Trade Centre (United Nations, 2010)
Guide to trade remedy procedures (anti-dumping, countervailing and safeguard) outlines scope of United States trade remedy laws; provides an overview of the procedural framework for anti-dumping and countervailing investigations in the country; addresses the chronology of a typical proceeding in defending a company’s interest by the US Department of Commerce; deals with anti-dumping investigations involving issues related to production cost; explains special rules utilized by the US Department of Commerce in anti-dumping cases against non-market economy countries; covers countervailing duties, and measuring subsidies; global safeguard measures and China-specific restrictions on fair trade; intellectual property protection, market access and trade policy issues; reviews the theory and practice of verification; issues that arise in injury investigations; post-order issues; settlement of trade disputes, as well as judicial and WTO appeals.